Comparison of Rifampicin Drug Susceptibility Determined by Conventional Culture Method and Pcr-Heteroduplex Analysis in Mycobacterium Tuberculosis Strains (Annals of Medical Research, 2021)
None
Keywords: M. tuberculosis, Rifampicin Resistance, PCR-Heteroduplex Analysis, Proportional Method.